A Casa da Avó: Projecto: Tempo e Memória - Ângela Machado Meireles (2016)
The presented dissertation focuses on the development of an intervention project for a group of buildings with a housing and agricultural character, placed in the property of Helena Grandmother's house, located in Madalena, parish and municipality of Paredes, in the Oporto's district. Through the extensive work of investigation as well as a building survey, it was primarily sought to rediscover childhood places and analyze the pre-existing buildings, as well as the surroundings in which they belong, to restore its history and to study their architectural and constructional characteristics, in order to define an appropriate and consistent method of intervention. Combining the previously mentioned analysis and interpretation method with the author's experience and personal perspective, the way in which the old house, uninhabited for the last fifteen years, could be restored was questioned and reflected upon, constituting a practical component of response in the form of a project.